This action might not be possible to undo. Are you sure you want to continue?

Part 3 - Images and Pre-images of Sets

Amber Habib Department of Mathematics Shiv Nadar University

Abstract Notes for the Precalculus course taught to 1st year students of the B.S. Mathematics program.

1

Images of Sets

Deﬁnition 1.1 Let f : X → Y and A ⊆ X. Then the image of A under f , denoted f (A), is the set deﬁned by: f (A) = {f (a) : a ∈ A}

A

f (A)

Example 1.2 Consider exp : R → R+ . Then, exp({0}) = {1} exp([0, ∞)) = [1, ∞) exp(R) = R+ 2 Exercise 1.3 Let f : X → Y and A ⊆ B ⊆ X. Then f (A) ⊆ f (B). Exercise 1.4 Let f : X → Y . Then f (∅) = ∅. 1

Exercise 1.5 Let f : X → Y . Then f is onto iﬀ f (X) = Y . Exercise 1.6 Provide a function f : R → R such that f (R) = [−2, 2] and f (Z) = {0}. Exercise 1.7 Let T : R2 → R2 be deﬁned by T (x, y) = (−y, x). Show that 1. T (X-axis) = Y-axis and T (Y-axis) = X-axis. 2. T rotates straight lines by right angles. 3. T maps a circle to a circle with the same radius. Exercise 1.8 Let T : R2 → R2 be a linear map, i.e. it has the form T (x, y) = (ax + by, cx + dy), Show that: 1. T is a bijection iﬀ ad − bc = 0. 2. If ℓ is a straight line in R2 then T (ℓ) is a straight line or a point. Theorem 1.9 Let f : X → Y and A, B ⊆ X. Then f (A ∪ B) = f (A) ∪ f (B) Proof: Since A, B ⊆ A∪B we have f (A), f (B) ⊆ f (A∪B). Hence f (A)∪f (B) ⊆ f (A∪B). For the other inclusion, begin with with y ∈ f (A∪B). Then ∃x ∈ A∪B such that f (x) = y. Then x ∈ A∪B =⇒ x ∈ A or x ∈ B =⇒ y ∈ f (A) or y ∈ f (B) =⇒ y ∈ f (A)∪f (B) Hence f (A ∪ B) ⊆ f (A) ∪ f (B). The corresponding result for intersection turns out to be false: Example 1.10 Consider X = {a, b}, Y = {1} and f : X → Y deﬁned by f (a) = f (b) = 1. Let A = {a} and B = {b}. Then f (A ∩ B) = f (∅) = ∅ but f (A) ∩ f (B) = {1} ∩ {1} = {1}. 2 Exercise 1.11 Produce a counterexample to f (A ∩ B) = f (A) ∩ f (B) using the function f : R → R, f (x) = x2 . We do have the following partial results: Theorem 1.12 Let f : X → Y and A, B ⊆ X. Then f (A ∩ B) ⊆ f (A) ∩ f (B) 2 2 (a, b, c, d ∈ R)

Proof: A ∩ B ⊆ A, B implies f (A ∩ B) ⊆ f (A), f (B).

2

Theorem 1.13 Let f : X → Y . Then f (A ∩ B) = f (A) ∩ f (B) for every A, B ⊆ X iﬀ f is one-one. Proof: Let f be one-one. We have to show that f (A) ∩ f (B) ⊆ f (A ∩ B). Suppose y ∈ f (A) ∩ f (B). Then ∃a ∈ A and ∃b ∈ B such that f (a) = f (b) = y. Since f is one-one we have a = b, and so a ∈ A ∩ B. Therefore y = f (a) ∈ f (A ∩ B). Now, assume the equality for all A, B. Let f (a) = f (b) = y. Deﬁne A = {a} and B = {b}. Then f (A) ∩ f (B) = f (A ∩ B) =⇒ {y} = f (A ∩ B) =⇒ A ∩ B = ∅ =⇒ a = b 2 The fact that a function preserves unions is valid for a union of any amount of sets: Theorem 1.14 Let f : X → Y . Let Aη be subsets of X, with the index η varying over a set E. Then f ( ∪ Aη ) = ∪ f (Aη )

η∈E η∈E

Proof: We just adapt the proof of the theorem for two sets. First, let y ∈ f (∪η∈E Aη ). Then y = f (x) for some x ∈ ∪η∈E Aη . Hence ∃η0 ∈ E such that x ∈ Aη0 . But then y ∈ f (Aη0 ) ⊆ ∪η∈E f (Aη ). This establishes f ( ∪ Aη ) ⊆ ∪ f (Aη )

η∈E η∈E

Next, let y ∈ ∪η∈E f (Aη ). Then ∃η0 ∈ E such that y ∈ f (Aη0 ). Hence y = f (x) for some x ∈ Aη0 . Then we have x ∈ ∪η∈E Aη and so y = f (x) ∈ f (∪η∈E Aη ). This shows f ( ∪ Aη ) ⊇ ∪ f (Aη )

η∈E η∈E

2 Exercise 1.15 Let f, g : X → Y with f (A) = g(A) for every A ⊆ X. Show that f = g. Exercise 1.16 Is the following true: If f, g : R → R with f (I) = g(I) for every open interval I, then f = g.

3

2

Pre-images of Sets

Deﬁnition 2.1 Let f : X → Y and C ⊆ Y . Then the pre-image of C under f , denoted f −1 (C), is the set deﬁned by: f −1 (C) = {x ∈ X : f (x) ∈ C} It must be noted that this deﬁnition does not require the inverse function f −1 to exist. f −1 (C)

C

Example 2.2 Let f : R → R, f (x) = x2 . Then f −1 (R) = R f −1 (R+ ) = R f −1 ({1}) = {−1, 1} f −1 ([−1, 1]) = [−1, 1] f −1 ([0, 1]) = [−1, 1] 2 Exercise 2.3 Let f : X → Y . Then f −1 (∅) = ∅ and f −1 (Y ) = X. Exercise 2.4 Produce a function f : R → R such that f −1 ((0, 2)) = R and f −1 ({0}) = Z. The act of taking pre-images is well-behaved with respect to both union and intersection: Theorem 2.5 Let f : X → Y and C, D ⊆ Y . Then f −1 (C ∪ D) = f −1 (C) ∪ f −1 (D) Proof: x ∈ f −1 (C ∪ D) ⇐⇒ ⇐⇒ ⇐⇒ ⇐⇒ f (x) ∈ C ∪ D f (x) ∈ C or f (x) ∈ D x ∈ f −1 (C) or x ∈ f −1 (D) x ∈ f −1 (C) ∪ f −1 (D) 2 4

Theorem 2.6 Let f : X → Y and C, D ⊆ Y . Then f −1 (C ∩ D) = f −1 (C) ∩ f −1 (D) Proof: Essentially identical to previous proof. Left for you to ﬁll in. 2

Both these theorems are true for unions and intersections of any amount of sets: Theorem 2.7 Let f : X → Y . Let Cη be subsets of Y , with the index η varying over a set E.Then 1. f −1 ( ∪ Cη ) = ∪ f −1 (Cη )

η∈E η∈E

2. f −1 ( ∩ Cη ) = ∩ f −1 (Cη )

η∈E η∈E

Proof: Left for you! Exercise 2.8 Let f : X → Y . Then 1. f −1 (f (A)) ⊇ A for every A ⊆ X. 2. f (f −1 (C)) ⊆ C for every C ⊆ Y

2

Exercise 2.9 Give examples where the inequalities in the previous exercise are strict. Exercise 2.10 Let f : X → Y . Show that f −1 (f (A)) = A for every A ⊆ X iﬀ f is one-one. Exercise 2.11 Let f : X → Y . Show that f (f −1 (C)) = C for every C ⊆ Y iﬀ f is onto. Theorem 2.12 Let f : X → Y and g : Y → Z, with C ⊆ Z. Then (g ◦ f )−1 (C) = f −1 (g−1 (C)) Proof: First, let x ∈ (g ◦ f )−1 (C). Let y = f (x). Then g(y) = g(f (x)) = (g◦f )(x) ∈ C implies f (x) = y ∈ g−1 (C), and hence x ∈ f −1 (g−1 (C)). Therefore (g ◦ f )−1 (C) ⊆ f −1 (g−1 (C)). Next, let x ∈ f −1 (g−1 (C)). Then f (x) ∈ g−1 (C). Therefore (g ◦ f )(x) = g(f (x)) ∈ C. Hence x ∈ (g ◦ f )−1 (C). This shows f −1 (g−1 (C)) ⊆ (g ◦ f )−1 (C). 2 Exercise 2.13 Let f, g : X → Y with f −1 (C) = g−1 (C) for every C ⊆ Y . Show that f = g. Exercise 2.14 Is the following true: If f, g : R → R with f −1 (I) = g−1 (I) for every open interval I, then f = g.

5

- Fozia Qazi
- Rashmi Kathuria
- Jayasree Subramanian
- I K Rana
- Haneet Gandhi
- Anita Sharma
- Shreya Khemani, Jayasree Subramanian
- R Srikanth
- Pramod Maithil
- P K Chaurasia
- Nidesh Soni, Ghanshyam Tewari
- Jayasree Subramanian
- Jasneet Kaur, Mohd Mamur Ali, Ashu Threja
- Himani Asija
- Ashu Threja
- Anchal Arora
- Cardinality_2
- Cardinality_1
- SNU-Precalculus-2011-Assgt2
- Logic 2
- Logic 1
- Assignment 1
- Functions 2
- Functions 1

Sign up to vote on this title

UsefulNot useful- Cardinality_2
- Logic 2
- Functions 1
- Functions 2
- Cardinality_1
- Logic 1
- Ergodic Decomposition
- James Cummings and Saharon Shelah- Cardinal invariants above the continuum
- Probability Essentials
- Saharon Shelah- On CH + 2^aleph-1->(alpha)^2-2 for alpha<omega-2
- 1004.0723
- P. C. Eklof, A. H. Mekler and S. Shelah- Uniformization and the Diversity of Whitehead Groups
- Saharon Shelah and Alexander Usvyatsov- More on SOP1 and SOP2
- Saharon Shelah and Andres Villaveces- Toward categoricity for classes with no maximal models
- Appendix Week07
- Saharon Shelah and Rami Grossberg- On Cardinalities in Quotients of Inverse Limits of Groups
- James Cummings and Saharon Shelah- Some independence results on reflection
- Saharon Shelah and Mor Doron- Bounded m-ary Patch-Width Are Equivalent for m≥3
- 79-112-1-PB
- Uniformly Continuous Function on a Normed Group
- Recursive Sets
- 1306.6682
- Jorg Brendle and Saharon Shelah- Evasion and prediction II
- A Class of Recursive Sets
- 2006 Spring Notes
- Saharon Shelah- The Pair (ℵn, ℵ0) May Fail ℵ0-Compactness
- Saharon Shelah and Lee J. Stanley- Forcing Many Positive Polarized Partition Relations Between a Cardinal and its Powerset
- ch2.pdf
- Good Pairs of Adjacency Relations in Arbitrary Dimensions
- Mirna Dzamonja and Saharon Shelah- On ◅^*-Maximality
- Functions 3

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue reading from where you left off, or restart the preview.

scribd